2018
DOI: 10.1371/journal.pone.0202341
|View full text |Cite
|
Sign up to set email alerts
|

Predicting segregation of multiple fruit-quality traits by using accumulated phenotypic records in citrus breeding

Abstract: In the breeding of citrus (Citrus spp.), suitable fruit quality is essential for consumer acceptance of new cultivars. To identify parental combinations producing F1 progeny with fruit-quality traits exceeding certain selection criteria, we developed a simple and practical method for predicting multiple-trait segregation in an F1 progeny population. This method uses breeding values of parental genotypes and an additive genetic (co)variance matrix calculated by the best linear unbiased prediction method to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For the prediction of cross mean, overall PA was 0.32 in scenario 2, equivalent to the average per-cross PA (0.29), while the average per-trait PA was twice as high (0.6) (Figure 3). In other studies concerning other plant crops, the average per-cross PA was not reported 5,6,7,8 , probably because, in most cases, there were not enough traits to estimate it. Bernardo et al 5 and Osthushenrich et al 6 also reported a high-average per-trait PA, above 0.9, while Yamamoto et al 8 reported PA values from 0.21 to 0.57 depending on the trait.…”
Section: Range Of Pa Valuesmentioning
confidence: 93%
See 1 more Smart Citation
“…For the prediction of cross mean, overall PA was 0.32 in scenario 2, equivalent to the average per-cross PA (0.29), while the average per-trait PA was twice as high (0.6) (Figure 3). In other studies concerning other plant crops, the average per-cross PA was not reported 5,6,7,8 , probably because, in most cases, there were not enough traits to estimate it. Bernardo et al 5 and Osthushenrich et al 6 also reported a high-average per-trait PA, above 0.9, while Yamamoto et al 8 reported PA values from 0.21 to 0.57 depending on the trait.…”
Section: Range Of Pa Valuesmentioning
confidence: 93%
“…Under an additive framework, cross mean is expected to be the sum of the breeding values of parents, but some deviation may result from dominance or epistasis 4 . So far, a few studies only have investigated cross mean PA 5,6,7,8 , although none of them clearly investigated its influencing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Association mapping can detect QTLs in citrus. Imai et al [35] detected seven QTLs comprising four novel ones including four important QTLs for fruit weight and one QTL for each, i.e., fruit skin color and pulp firmness through genotyping-by-sequencing. The development of high resolution genomic map of citrus provides greater significance to plant breeders and to link genomic regions with desired traits.…”
Section: Citrusmentioning
confidence: 99%
“…The breeding of citrus plants through classical breeding methods has been used for a long time (Inglese and Sortino 2019). Such methods have been successfully applied over decades to generate new and better citrus cultivars with improved fruit quality, enhanced disease resistance and increased tolerance to environmental stresses (Uzun et al 2015;Bastianel et al 2018;Deng 2008;Gois et al 2016;Huang et al 2018;Imai et al 2018;Ruiz et al 2018;Shimada et al 2017). However, despite its unquestionable and invaluable contribution to citrus production worldwide and to the citrus industry, traditional citrus breeding is invariably a very laborious process that takes many years to be accomplished, mostly due to the reproductive biology and long juvenile phase of citrus plants (Iglesias et al 2007).…”
Section: Genetic Engineering For Canker Resistance In Citrus Plantsmentioning
confidence: 99%